2022
DOI: 10.3389/fnins.2022.834507
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive Vagus Nerve Stimulation in Treatment of Disorders of Consciousness – Longitudinal Case Study

Abstract: Neuromodulatory electroceuticals such as vagus nerve stimulation have been recently gaining traction as potential rehabilitation tools for disorders of consciousness (DoC). We present a longitudinal case study of non-invasive auricular vagus nerve stimulation (taVNS) in a patient diagnosed with chronic unresponsive wakefulness syndrome (previously known as vegetative state). Over a period of 6 months we applied taVNS daily and regularly evaluated the patient’s behavioral outcomes using Coma Recovery Scale – Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(40 citation statements)
references
References 48 publications
0
40
0
Order By: Relevance
“…[ 20 , 23 25 , 28 , 33 , 35 ] Since the first study by Yu et al in 2017, 6 studies on the application of taVNS in patients with DOC have been reported. [ 23 , 28 , 33 , 35 – 37 ]…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…[ 20 , 23 25 , 28 , 33 , 35 ] Since the first study by Yu et al in 2017, 6 studies on the application of taVNS in patients with DOC have been reported. [ 23 , 28 , 33 , 35 – 37 ]…”
Section: Introductionmentioning
confidence: 99%
“…In 2022, Osińska et al [ 33 ] reported the case of a patient who showed recovery of impaired consciousness after 6 months of taVNS treatment. A 28-year-old woman was diagnosed with persistent VS at 4 points on the CRS-R following TBI which occurred 6 years previously.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations